2022
DOI: 10.21037/atm-22-1812
|View full text |Cite
|
Sign up to set email alerts
|

Identification of autophagy-related genes as potential biomarkers for type 1 diabetes mellitus

Abstract: Contributions: (I) Conception and design: ZF Wang; (II) Administrative support: ZF Wang; (III) Provision of study materials or patients: B Yang; (IV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Autophagy is a form of autophagic cell death that recycles and recirculates nutrients by degrading damaged intracellular cytoplasm, organelles and protein aggregates and invading pathogens through the lysosomal pathway. 11 , 14 Moderate autophagy can help maintain the number and the normal morphological structure of islet β-cells in the body with normal function. 15 Autophagy can also delay apoptosis of pancreatic β-cells, while it can further protect pancreatic β-cells by adaptively reducing endoplasmic reticulum stress and then enhancing the survival of pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a form of autophagic cell death that recycles and recirculates nutrients by degrading damaged intracellular cytoplasm, organelles and protein aggregates and invading pathogens through the lysosomal pathway. 11 , 14 Moderate autophagy can help maintain the number and the normal morphological structure of islet β-cells in the body with normal function. 15 Autophagy can also delay apoptosis of pancreatic β-cells, while it can further protect pancreatic β-cells by adaptively reducing endoplasmic reticulum stress and then enhancing the survival of pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Furthermore, T1DM has been confirmed that it is related to various molecular mechanisms, including autophagy, oxidative stress, inflammation and apoptosis of pancreatic β-cells. [11][12][13] Yet, though significant advances have been made since the past several decades, the potential therapeutic strategies and the exact molecular mechanisms of T1DM remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%